Extractability of carcinogenic toxins in brewed beverages (tea) a study by hyphenated plasma mass spectrometry - Pillay, Avin; Stephen, Sasi; Manuel, Johnson (International Journal of Engineering and Technology, 2019)
Beryllium (Be) and arsenic (As) are noted for their potential carcinogenicity, and their elemental distribution in brewed teas was the subject of investigation. A study of this nature, where carcinogens are extracted by boiling, is underexplored. The study focused on brewed beverages and the experimentally determined concentrations were thus compared with drinking water levels. Tea is a favourite drink, is consumed several times a day and toxins could bio-accumulate in the body. Appreciable concentrations of carcinogens could therefore, affect the human body and restorative measures could be adopted to minimize such toxins in tea leaves. Eight brands of tea samples were procured and investigated for carcinogens after brewing in ultrapure Millipore water. Hyphenated plasma mass spectrometry (ICP-MS) was deployed to probe the levels of the elements of interest. The operation of the instrument was certified with reference standards. Aberrations in performance were reset by use of an internal standard. Beryllium levels occurred in the range 0.5-1.5 Î¼g/L; As concentrations were between 1-3 Î¼g/L. The distribution of the selected elements is discussed. These carcinogens could emerge from the ground and from the agricultural water used to cultivate the tea leaves, or alternatively, from the manufacturing processes associated with their production. It could be feasible to deploy the data to identify or â€œfingerprintâ€ the country or region of origin of the corresponding tea sample. This study could definitely be considered a source of reference data, and could add to the growing knowledge on sustainable development.Â Â Â